Blurred boundaries of the brain-1 (Aide-memoire for patient narrative) - Dutta, Ashish; Paudel, Raju; Thapa, Lekh Jung; Bhattarai, S; Shrestha, MA; Shrestha, M (Journal of Psychiatrists' Association of Nepal, 2023)
Background: This is a case series of clinical cases presenting to our Neuropsychiatry Center, who were either referred by physicians or approached to seek treatment on their own. They were receiving treatment since few years. No improvement in symptom were primary reason for referral and consultation with our team. Re-evaluation in realms of Neurology and Psychiatry depicted the missed link in diagnostic and therapeutic approaches exercised previously. The intent to reflect upon novel findings is not to undermine the effort applied in clinical evaluation by prior physicians, but to reflect few observations which may have been inadvertently missed during routine assessment. This serves as as an aide-memoire to history taking and suggestions to remain well informed and updated in our approach to service seekers. Abstract: Symptom overlap and comorbidities are commonly encountered in clinical practice of Psychiatry or Neurology. Many neurologic disorders have psychiatric symptoms (e.g., depression in patients following a stroke or with multiple sclerosis or Parkinson’s disease), and many psychiatric disorders have been associated with neurologic symptoms (e.g., movement disorders in schizophrenia). This overlap occurs mostly because brain is the source common for both neurological and psychiatric illness and on multiple occasion it becomes difficult to delineate the boundary, leading to diagnostic dilemmas, followed by inappropriate management strategies. Patients and family members suffer for long periods of time in trying to understand the disease phenomenon and prognosis. In this case series, we present 3 cases of clinical interest across different framework of clinical presentation and assessment for e.g, neurological illness being managed as psychiatric illness or scenarios where both neurological and psychiatric illness coexisted but only one aspect was addressed. Re-assessment and work up by a team of neurologists and psychiatrist lead to clarification of the boundaries (at least in these cases who underwent prolonged sufferings owing to lack in clarity of pathology) with precise diagnosis generating improved outcomes in functionality and satisfaction. The diagnosis of neuropsychiatric disorders is performed by psychiatrists through diagnostic interviews, and categorization of patients based on diagnostic and classification manual (ICD-10, DSM-5) which are syndrome/symptom based. Although this has been a standard practice, often error may occur in diagnosing illnesses falling under the wider realm of neurology and psychiatry. Some presenting symptoms may be assumed being part of neurological illness or of functional origin, or mixed states and many may be overlooked during routine clinical assessment.